Fixed-Point Results Related to b-Intuitionistic Fuzzy Metric Space - Mohamed Altanji; Annamalai Santhi; Vediyappan Govindan; Shyam Sundar Santra; Samad Noeiaghdam (Journal of Function Spaces)
In this study, we contribute to the terminological debate about various fixed-point results’ use of the term intuitionistic fuzzy b-metric space in defining the structure based on fuzzy sets. As a predominant result, we give an adequate condition for a sequence to be Cauchy in the intuitionistic fuzzy b-metric space. Subsequently, we simplify the proofs of manifold fixed-point theorems in the intuitionistic fuzzy b-metric spaces under the prominent contraction conditions. Also, we give a satisfactory condition for a solution to Cauchy in the intuitionistic fuzzy b-metric spaces.